2018
DOI: 10.13057/biodiv/d190228
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of four giant gourami strains from Java and Sumatra

Abstract: Nuryanto A, Amalia G, Khairani D, Pramono H, Bhagawati D. 2018. Molecular characterization of four giant gourami strains from Java and Sumatra. Biodiversitas 19: 528-534. Giant gourami (Osprhonemus goramy) are widely distibuted across Indonesia, such Java, Sumatra, and Kalimatan which lead to the emerge of various gourami strains due to morphological differences. However, no scientific data about the relationship between morphological and genetic differences among strains. This research aimed to obtain informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
12
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 25 publications
6
12
0
1
Order By: Relevance
“…This uniqueness leads to different size when it is amplified from different species. Our result showed similar case to several previous studies where different length of the COI gene PCR products were resulted from different fish species (Nuryanto et al, 2018;Barbuto et al, 2010).…”
Section: Resultssupporting
confidence: 92%
“…This uniqueness leads to different size when it is amplified from different species. Our result showed similar case to several previous studies where different length of the COI gene PCR products were resulted from different fish species (Nuryanto et al, 2018;Barbuto et al, 2010).…”
Section: Resultssupporting
confidence: 92%
“…It can be difficult to characterize the different strains of giant gourami reared in Indonesia because their vernacular names vary according to localities. Currently, more research is being conducted to improve strain characterization (Azrita & Syandri, ; Nuryanto, Amalia, Khairani, Pramono, & Bhagawati, ). Interviewed farmers ( n = 38) reported that they own between one and four different strains of broodfish.…”
Section: Resultsmentioning
confidence: 99%
“…In the Bogor district, the situation is more complex. Although there is a dominant strain called “Bastar” (Nuryanto et al, ) used by 68% of farmers ( n = 15), other strains coexist and are used in variable proportions.…”
Section: Resultsmentioning
confidence: 99%
“…The power of this gene as a species barcode marker because it is changeable enough (Nuryanto et al, 2007;Nuryanto and Kochzius, 2009) due to its high mutation rate which is higher compared to other mitochondrial genome (Hebert et al, 2003). Clear separation of different species and above species category was also reported in fish larvae (Nuryanto et al, 2017), or even among strain within species (Nuryanto et al, 2018).…”
Section: Homology Test and Genetic Species Conceptmentioning
confidence: 94%
“…These observed high values of inter-species genetic divergences are common phenomena. Several studies also reported high genetic divergences among species in various animal groups, such as in fish (Peg et al, 2006;Pereira et al, 2013;Nuryanto et al, 2017;Nuryanto et al, 2018); and Crustacea (Barber et al, 2002).…”
Section: Homology Test and Genetic Species Conceptmentioning
confidence: 97%